The contributing factor to underemployment among business graduates UiTM Melaka Campus / Noorashikin Mohd Idris and Siti Sarah Nur Aiman Abdullah Bukhari - Mohd Idris, Noorashikin; Abdullah Bukhari, Siti Sarah Nur Aiman (Faculty of Business and Management, 2014)
The purpose of this study was to determine the significance factors that influence underemployment among business graduates in UiTM Melaka Campus. The variables consist of demand and supply of labor market, marketability of degree, societal factor and job satisfaction that are stated as independent variables for this study and the dependent variable is underemployment. The finding showed that demand and supply of labor market, marketability of degree and job satisfaction have a significant influence to on underemployment among business graduates in UiTM Melaka Campus while societal factor showed no significant relationship to underemployment. This study refers to primary data that was used to support the sampling technique. Meanwhile, the researcher used questionnaire as the method to collect all the data from sample respondents in order to achieve the research objectives. While the data for this study was analysed using multiple statistical procedures: mean point value, standard deviation, and correlation analysis. The result of the study presented in this research agrees that demand and supply of labor market, marketability of degree and job satisfaction influenced underemployment among graduates. This study can be seen as a foreword to a more detailed study to be carried out by future research on the issue of underemployment among graduates in Malaysia.